Proceedings - Rankine, Lloyd B. (UWI. Department of Agricultural Economics and Farm Management St AugustineTT, 1986)
Sees agribusiness as the way forward for Caribbean agriculture. Discusses theoretical concepts in agribusiness and examines its relationship with commodity organizations. Reviews the applications of computers to agribusiness and assesses the Caribbean's training and research needs in this area. Examines ways of developing agro-industrial enterprises and of using regional technology in agribusiness. Contains papers on several aspects of the fisheries and livestock sub-sectors. Includes papers on production, marketing, and non-traditional agriculture.